Viperhand - Niles, Douglas (Lake Geneva, Wisconsin : TSR, 1990)
"Erix, the former slave girl, and Halloran, the legionnaire, flee from the waves of catastrophe sweeping Maztica. The God of War feast upon chaos while the desperate lovers strive to escape from enemies on all sides."--Cover.
Keywords: Forgotten realms (Imaginary place) -- Fiction; Science fiction